Systemic Immun e–Inflammation Index as a Predictor for Head and Neck Cancer Prognosis: A Meta-Analysis - Wang, Yun-Ting; Kuo, Liang-Tseng; Weng, Hsu-Huei; Hsu, Cheng-Ming; Tsai, Ming-Shao; Chang, Geng-He; Lee, Yi-Chan; Huang, Ethan I.; Tsai, Yao-Te (Frontiers in Oncology, 2022)
Background Studies have reported inconsistent results regarding the prognostic value of the systemic immune–inflammation index (SII) in head and neck cancer (HNC). Thus, the present meta-analysis assessed the literature on the prognostic value of SII in those with HNC. Methods The Cochrane Library, EMBASE, and PubMed databases were searched, and study methodological quality was assessed using the Newcastle–Ottawa quality assessment scale. To determine the association of the SII with survival outcomes, pooled hazard ratios (HRs) as well as the associated 95% confidence intervals (CIs) were used. To assess the associations of the SII with clinicopathological features, the odds ratios (ORs) and corresponding 95% CIs were considered. Begg’s funnel plot and Egger’s linear regression test were used to assess publication bias. Results A total of 12 studies that together enrolled 4369 patients with HNC were analyzed. In the pooled results, a high pretreatment SII was correlated with poorer overall survival (HR = 2.09, 95% CI = 1.62–2.70, p < 0.001), disease-free survival (HR = 2.79, 95% CI = 1.99−3.89, p < 0.001), and progression-free survival (HR = 1.80, 95% CI = 1.30−2.48, p < 0.001). A stratified analysis indicated that SII for overall survival was applicable regardless of tumor site, treatment modality, overall stage, sample size, SII cutoff, and method for determining the SII cutoff. Furthermore, a high SII was correlated with a more advanced T classification (OR = 1.14, 95% CI = 1.09–1.18, p < 0.001) and nodal metastasis (OR = 1.55, 95% CI = 1.18–2.05, p = 0.002) in patients with HNC. Conclusions An elevated pretreatment SII predicts more advanced tumor and nodal status and poorer survival outcomes in cases of HNC. Because the measurement of SII is convenient and its use is cost-effective, we suggest that it can be applied by clinicians in the management of HNC.